2010
DOI: 10.1177/1063426609353607
|View full text |Cite
|
Sign up to set email alerts
|

Teacher—Student Relationships Among Behaviorally At-Risk African American Youth From Low-Income Backgrounds: Student Perceptions, Teacher Perceptions, and Socioemotional Adjustment Correlates

Abstract: This investigation examines teacher—student relationships among African American youth from low-income backgrounds (N = 193). Students and their teachers completed measures of teacher—student relationship quality and measures pertaining to emotional, behavioral, and school-related adjustment. Results indicated that African American youth who fell above the clinical cut point on the externalizing scale of the Child Behavior Checklist (n = 64) reported lower trust in relationships with teachers than did similarl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
63
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 55 publications
6
63
0
1
Order By: Relevance
“…Often, these were a type of student who showed little engagement and interest for school subjects, created unrest and noise, and took the focus away from teaching in the classroom. In keeping with past research (Murray & Murray, 2004;Murray & Zvoch, 2011), our findings suggest that it was particularly difficult to achieve closeness and contact with male students, especially in the VQ programs where the dropout rate is documented to be highest . Some teachers expressed a wish to focus on the specific subjects more than spend time on the social processes and relationship establishment.…”
Section: Discussionsupporting
confidence: 87%
“…Often, these were a type of student who showed little engagement and interest for school subjects, created unrest and noise, and took the focus away from teaching in the classroom. In keeping with past research (Murray & Murray, 2004;Murray & Zvoch, 2011), our findings suggest that it was particularly difficult to achieve closeness and contact with male students, especially in the VQ programs where the dropout rate is documented to be highest . Some teachers expressed a wish to focus on the specific subjects more than spend time on the social processes and relationship establishment.…”
Section: Discussionsupporting
confidence: 87%
“…These results are in line with a recent study that found some concordance between teacher and adolescent student perceptions for the positive dimensions of relationships (Murray & Zvoch, 2011). For the remaining 28 students, boys' and teachers' perceptions did not match.…”
Section: Some Mismatch In the Perceptions Of Boys And Teacherssupporting
confidence: 89%
“…When they are reported, findings have been inconsistent. In a study with kindergarten children, low correlations were found between student and teacher ratings of support, closeness and conflict (Murray, Murray, & Waas, 2008), whereas in a study with at-risk, urban youth, there were indications of some concordance between teacher and student perceptions for the positive dimensions of relationships (Murray & Zvoch, 2011). The diversity of findings suggest that what is important for student-teacher relationships may depend on whether the perspective of the students or the teachers is considered.…”
mentioning
confidence: 93%
“…Not surprisingly, social learning-related research indicates that negative parenting (e.g., criticizing, making negative statements, and/or rejecting) is associated with child behavioral problems (Webster-Stratton & Hammond, 1999), whereas positive parenting (e.g., responsiveness, praise) promotes social skills and reduces behavioral problems (Webster-Stratton, Reid, & Hammond, 2001). Notably, there is also evidence that children with such behavioral problems develop poorer relationships with their teachers (Henricsson & Rydell, 2004;Murray & Zvoch, 2011).…”
Section: Determinants Of the Student-teacher Relationshipmentioning
confidence: 99%